(untitled) (Journal of Philosophy Culture and Political Science, 2015)
Inthe article author claims thought that the problem of a ratio of consciousness and unconscious, investigated by S. Freud, has to be considered in a foreshortening of social contradictions. Many,following from the essence of the human being the aspirations of personality to his or her freedom, development, manifestations and statements it as special individuality in the conditions of social alienation, are exposed, on Freud’s terminology, to repression. Individuals find illusory ways of permission of the internal conflicts at their individual level.